Reading Comprehension Difficulties Encountered by English Students of Islamic University of Riau - Satriani, Estika (Program Studi Pendidikan Bahasa Inggris FKIP UIR, 2018)
The aim of this research is to find out the difficulties  of reading comprehension  faced by the first semester of students in FKIP UIR Pekanbaru. Kualitative research design in case study used in this research by using the instruments were  questionnaire and  interview guide. Based on the results of analyzing  data from the questionnaire and interview, the reseacher   found  most of students’ difficulties in reading comprehension because they have no motivation in reading habit, they  read a little or nothing. It is considered to be a problem for the students to comprehend a reading text. Another students’  difficulties in reading comprehension was the low reading skill. The students complained about the fact that they found, they need to study hard to remember the information they just read. They also need much time to read the text to overcome their problem. Too difficult reading material is also one of students problem in understanding the reading text. The material of reading is unfamiliar for them and grammatical complexity is also a reason why the students failed to comprehend the text correctly. The sentences in reading text too long or having complicated sentences. Related with these problem, new words  and long texts are seen by the students as a major  obstacle to comprehend a reading text.